A study on the validity of the end-term achievement tests on English grade 12, High Schools in Northern Vietnam. M.A Thesis Linguistics - Hoàng, Văn Sáu (ĐHNN, 2017)
Chapter 1 is the introduction that presents such initial information as the rationale, aims, methods, research questions and the organization of the study. Chapter 2 reviews all related literature that provides the theoretical basis for language testing and language evaluation. Chapter 3 is the main part of the study which shows the research design containing research questions, data description, informants and analytical framework. Next, data analysis of construct validity and content validity is discussed. Finally, the findings about content validity and construct validity of the test samples are laid out. Chapter 4 offers the conclusions that make clear the research questions. Some implications are suggested to improve end -term achievement tests in terms of their construct validity and content validity. The limitations and directions to further research are also mentioned in this final chapter.